[Au14(PPh3)8(NO3)4]: An Example of a New Class of Au(NO3)‐Ligated Superatom Complexes1. Issue 12 (18th February 2013) - Gutrath, Benjamin S.; Oppel, Iris M.; Presly, Oliver; Beljakov, Igor; Meded, Velimir; Wenzel, Wolfgang; Simon, Ulrich
<x xml:space="preserve">Abstract</x> Golden beauty: For the first time a ligand‐stabilized Au14 cluster has been examined. The structure of this superatom complex bears several impressive and unique features, which will further support the understanding of certain guiding principles for molecular‐precision synthesis and functionalization of ultrasmall nanoparticles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>